Scolytodes Ferrari (Coleoptera, Scolytinae) from Ecuador: 40 new species, and a molecular phylogenetic guide to infer species differences - Jordal, Bjarte H.; Smith, Sarah M. (Zootaxa, 2020)
The genus Scolytodes Ferrari is a highly diverse group of Neotropical bark beetles. Recent collecting by hand and canopy fogging in Ecuador produced many new records. Overlap in species composition between samples from the canopy and the ground was very low, and canopy fogging revealed the highest proportion of undescribed species. Altogether we report records for 55 species of Scolytodes from Ecuador, including 40 species new to science: Scolytodes pseudoatratus Jordal and Smith, sp. nov., Scolytodes latipes Jordal and Smith, sp. nov., Scolytodes sloanae Jordal and Smith, sp. nov., Scolytodes samamae Jordal and Smith, sp. nov., Scolytodes otongae Jordal and Smith, sp. nov., Scolytodes chaplini Jordal and Smith, sp. nov., Scolytodes projectus Jordal and Smith, sp. nov., Scolytodes lubricus Jordal and Smith, sp. nov., Scolytodes inordinatus Jordal and Smith, sp. nov., Scolytodes cancellatus Jordal and Smith, sp. nov., Scolytodes jubatus Jordal and Smith, sp. nov., Scolytodes abbreviatus Jordal and Smith, sp. nov., Scolytodes stramineus Jordal and Smith, sp. nov., Scolytodes teres Jordal and Smith, sp. nov., Scolytodes animus Jordal and Smith, sp. nov., Scolytodes pseudoanimus Jordal and Smith, sp. nov., Scolytodes bombycinus Jordal and Smith, sp. nov., Scolytodes bisetosus Jordal and Smith, sp. nov., Scolytodes horridus Jordal and Smith, sp. nov., Scolytodes virgatus Jordal and Smith, sp. nov., Scolytodes criniger Jordal and Smith, sp. nov., Scolytodes pseudocrassus Jordal and Smith, sp. nov., Scolytodes semicrassus Jordal and Smith, sp. nov., Scolytodes pseudolepidus Jordal and Smith, sp. nov., Scolytodes semilepidus Jordal and Smith, sp. nov., Scolytodes fortis Jordal and Smith, sp. nov., Scolytodes peniculus Jordal and Smith, sp. nov., Scolytodes tristis Jordal and Smith, sp. nov., Scolytodes chrysifrons Jordal and Smith, sp. nov., Scolytodes amictus Jordal and Smith, sp. nov., Scolytodes cnesinoides Jordal and Smith, sp. nov., Scolytodes maestus Jordal and Smith, sp. nov., Scolytodes vietus Jordal and Smith, sp. nov., Scolytodes echinus Jordal and Smith, sp. nov., Scolytodes rufifrons Jordal and Smith, sp. nov., Scolytodes arcuatus Jordal and Smith, sp. nov., Scolytodes validus Jordal and Smith, sp. nov., Scolytodes sparsus Jordal and Smith, sp. nov., Scolytodes lapillus Jordal and Smith, sp. nov., Scolytodes coronatus Jordal and Smith, sp. nov. We also provide the first description of the female and a new country record for Scolytodes grandis (Schedl, 1962) (=Scolytodes glaberrimus Wood, 1972 syn. nov.) and a redescription and new country record for Scolytodes pilifrons (Schedl, 1962). The total number of valid species is now 287. Additional new country records were established for Scolytodes acuminatus Wood, 1969, Scolytodes comosus Jordal and Kirkendall, 2019, Scolytodes costabilis Wood, 1974, Scolytodes glabrescens Wood, 1972, Scolytodes impressus Wood, 1969, Scolytodes nitidus (Eggers, 1928), Scolytodes striatus (Eggers, 1934), Scolytodes tucumani Wood, 2007, and from another Hexacolini genus, Pycnarthrum fulgidum Wood, 1977. The first molecular phylogeny for Scolytodes is provided and used primarily to guide the inference of species validity. Molecular data from COI, 28S and EF-1α revealed substantial genetic divergence between morphologically very similar but diagnosable species.